2009
DOI: 10.1177/0021998309345342
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane Foams Obtained from Castor Oil-based Polyol and Filled with Wood Flour

Abstract: A natural polyol was prepared from castor oil by alcoholysis with triethanolamine. The oil and the oil-based polyol were characterized by infrared spectroscopy and through the analytical determination of their functional groups, both techniques indicating that the hydroxyl content increased significantly after the alcoholysis reaction. The modified oil was subsequently used as the polyol component in the formulation of rigid polyurethane foams. Wood flour was chosen to be incorporated as filler in these materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
115
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(132 citation statements)
references
References 33 publications
14
115
0
3
Order By: Relevance
“…During compression, distribution of external force inside the material is changing due to the changes of foams' cellular structure. Higher apparent density is obviously related to higher structural packaging, which additionally enhances the stiffness of material [35]. In the Fig.…”
Section: Resultsmentioning
confidence: 95%
“…During compression, distribution of external force inside the material is changing due to the changes of foams' cellular structure. Higher apparent density is obviously related to higher structural packaging, which additionally enhances the stiffness of material [35]. In the Fig.…”
Section: Resultsmentioning
confidence: 95%
“…They showed that foams made from 100% of castor oil were unstable and collapsed indicating the inferior reactivity of castor oil with isocyanate. The modification of castor oil increases its hydroxyl value and hard segment composition to improve the rigidity, physical and mechanical properties and crosslinking density of the final PU products [9]. Nevertheless, the hydroxyl value of modified castor oil is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Plastics can therefore be reinforced or filled with fibers without any significant effect on the density of the resulting polymer composites. Furthermore, the hydroxyl groups (-OH) on the surfaces of lignocellulosic fibers interact with isocyanate groups, leading to excellent interfacial bonding between fibers and polyurethane (Mosiewicki et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Racz et al (2009) focused on the production and characterization of lightweight PU composites reinforced with pine wood flour and showed that the strength, modulus, and storage modulus of the composites increased as the filler content increased. Mosiewicki et al (2009) used wood flour as a filler in rigid polyurethane and showed that the chemical reaction between wood flour and isocyanate strongly affected the composite response to thermogravimetric tests. The compression modulus and yield strength of the PU composites decreased as the wood flour content increased.…”
Section: Introductionmentioning
confidence: 99%